ME-VoLTE: Network functions for energy-efficient video transcoding at the mobile edge - Beck, Michael Till; Feld, Sebastian; Fichtner, Andreas; Linnhoff-Popien, Claudia; Schimper, Thomas (2015 18th International Conference on Intelligence in Next Generation Networks, 2015)
Encoding multimedia streams of video calls is a very compute-intense task that significantly decreases battery lifetime of mobile phones. This paper introduces an approach to reduce power consumption of mobile phones by offloading video encoding efforts from mobile devices to external services. These services are hosted on servers co-located with cellular base stations. The paper describes how these services are integrated into the existing mobile network architecture and presents a communication protocol for negotiating offloading settings. First measurement results indicate that power consumption of mobile devices is reduced by approximately 13%.